Transitional Spaces of a Community Center in Macau - Lin, Yanzi (University of Saint Joseph, 2024)
In a fast-paced and densely populated city, community activity centers can provide a social place for residents. This thesis is a study of this promise of social life for a new urban development in Macau. Community centers play an important role in promoting community cohesion and resident participation. Yet, public space for Macau residents is increasingly unable to meet growing and diversified needs. In what ways can the development of activity centers improve the quality of life of residents? Can transitional spaces between different functional areas in community centers play a more effective role in promoting social interaction within the community? The principal tasks of this thesis are as follows: (1) an in-depth examination of the impact of shared transitional spaces on the overall design of community activity centers, (2) a discussion of transitional spaces in community centers in terms of the functional efficiency of these centers and the interactive experience of users, and (3) articulation of principles and recommendations for the design of transitional spaces in community centers. Overall, this thesis argues that, by designing efficient and user-friendly shared transitional spaces, architects can better serve the community and its users, and foster a closer connection between architecture, people, and communities
Keywords: Community Centers; Social Interaction; Social Space; Theses and Dissertations Master of Architecture (MARCH); Transitional Spaces; University of Saint Joseph

FLOWING PATH: SPORTS CENTER AS SOCIAL CONNECTOR - Xin, Ziyan (University of Saint Joseph, 2024)
In the age of the information society, the prominence of internet communication and social media has meant that the role of face-to-face encounters in public life has been diminished. This trend has been exacerbated by public health concerns in the aftermath of the COVID pandemic. The social role of architecture and its contribution to the sustainability of interpersonal relationships has become a significant issue for architects. As a place to accommodate sporting activities and social space in the community, sports centers play an important role in promoting social cohesion and interaction. This is the focal topic of the present thesis. The principal tasks of this thesis are as follows: (1) This thesis collects and studies relevant literature on sports centers as social spaces. A special emphasis is placed on discussions of social spaces. The intention is to articulate design characteristics of community sports centers that merit further exploration. (2) This thesis selects three representative sports facilities as case studies and considers how they promote the formation of social bonds and interactions. The thesis offers a review of design ideas, planning strategies and specific methods of implementation. (3) This thesis takes the design project for a sports center in New District A in Macau as an example, and puts forward a design strategy of ""vertical intensification + shared application"". This strategy aims to promote the integration of the sports center with the urban environment, while creating a flexible public space that can adapt to the needs of spontaneous and social activities. The intention is to make the sports center a place that promotes community interaction and connectivity. Overall, this thesis argues that community sports centers can become important places to promote social interaction through well-designed architectural space. Specific design factors and strategies explored in this thesis provide useful points of reference for architects. Through on-going processes of optimization and innovation, sports centers can better serve the community of Macau
Keywords: Circulation strategies in architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; integrated sports facilities; social connectors; sports centers

A CONTEMPORARY VENUE FOR TRADITIONAL CANTONESE OPERA IN MACAO - Li, Zebin (University of Saint Joseph, 2024)
Cantonese opera has a long and profound history and has evolved over 700 years, making it unique and distinctive. In a diversified media and entertainment, Cantonese opera culture in Macao, like many other aspects of traditional Chinese cultures, is facing a general decline. Specific challenges include loss of audience, the decline and disintegration of professional groups, and reduced scope of the active repertoire. How can a new venue for traditional Cantonese opera promote a positive response to the contemporary challenges that threaten its cultural vitality? How can a new design approach respond to local issues and contemporary architectural production? Can programmatic diversification of a performance venue (cultural exchange, art display, education) be a useful strategy? This thesis consists of five parts. Part 1 of this thesis outlines the background of research, describes the purpose and significance of the research, and deal with issues of research method. Part 2 considers the artistic characteristics of Cantonese opera, including the spatial characteristics of traditional Cantonese opera theatres, the characteristics of Cantonese opera costumes, and the changing characteristics forms of performance. Part 3 is focused on the uses of parametric models in architectural design. Part 4 offers three case studies of opera houses in China, the Guangzhou Opera House, the Harbin Grand Theatre, and the Xiqu Centre in Hong Kong. Part 5, the core of this thesis, proposes a design of a new performance venue for Cantonese Opera House in Macao. Overall, this thesis offers an account of main considerations in the transformation process from traditional Cantonese opera venues to modern Cantonese opera houses and situates these considerations in the context of contemporary discussions of parametric architecture
Keywords: Architectural Parametric; Cultural Characteristics of Cantonese Opera; Design of Cantonese Opera House in Macao; Modern Opera House Design; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

THE MARKET AS SOCIAL LANDSCAPE IN MACAU - Ma, Jianjun (University of Saint Joseph, 2024)
Markets in Macau are not merely places for commercial retail, they are also social spaces. As a centre of communal life, markets are of great significance to the lives of Macau residents. However, with the rise of supermarkets and online shopping, the role of traditional markets has been reduced. At the same time, the messy and unkempt nature of traditional markets has become a negative factor of their social viability. The result has been a downward spiral of poor operation, decline in rental yield and loss of customers. Can the markets be revitalized for Macau residents? Can the social attributes of markets be reactivated? How can the experience of markets be re-imagined for different user groups? The present thesis is organized into 5 parts. The first part deals with the background of research. It also describes the purpose and significance of the research and discusses research methodology. The second part details market pressures in Macau, including insufficient land and space resources, poor sanitary environment, and tourism promotion needs. The third part examines the idea of “walkable cities” in terms of four concerns—usefulness, safety, comfort, and spatial interest—and in terms of specific case studies. The fourth part concerns a design project for a market at ZONE A in Macau. The thesis details the needs of a market in this zone and considers them in the light of the idea of walkable cities. Overall, this thesis attempts to contribute to public discussion of the future of markets in Macau in terms of service, socialisation and promotion
Keywords: Markets in Macau; Social Spaces; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; Walkable Cities

SPORTS FACILITIES IN HIGH-DENSITY URBAN AREA - Wong, Si Weng (University of Saint Joseph, 2023)
How can we provide more sports areas in a high-density urban environment? Nowadays, most cities in Asia are experiencing high-speed development (Satterthwaite, 2023). There is an intensely increasing demand for land that is confronted with an insufficient supply of space, resulting in a shortfall of suitable construction space to meet the rising demand. Over the past few decades, different countries and cities have created various solutions for this issue. This shortage of space has been resolved in various ways, for example: through land reclamation, renovation, and architectural design (Grydehoj, 2015). This dissertation seeks to analyse and discuss how architects have used design to expand spaces within the limited available areas for public spaces like sports facilities (Carmona, 2021). Understanding how sports modalities influence architecture and space utilisation for sports activities will also be covered. Additionally, it will examine case studies on how to better implement the program in a limited urban area with regards to the typology connections of sports facilities and their interaction with users. Finally, this dissertation is practice-based and oriented, the case study and project development will focus on a sports facility in the high-density populated Taipa Centre (Macau). This specific project solution will address the real problem for the city, and research will conclude by analysing the constraints of sports architecture in high-density areas, providing design solutions for these situations, and thereby contributing to the improvement of public spaces in a city
Keywords: Centrality; High-Density Urban Spaces; Indoor-Outdoor Interaction; Sports Facilities; Stacking; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

UNITING - FRAGMENTED SPACES ARCHITECTURE CENTRALIZING HERITAGE INTERPRETATION - Un, Cheng Wai (University of Saint Joseph, 2023)
For many people, an art museum is a place to display artifacts, artworks, and the temporaryhistory of a community or country. It also advocates for an artist’s viewpoints on art. In fact,museum design is closely related to politics. The purpose for building a museum in a city is toexhibit information about the development of the local culture. Moreover, high culturalvalue land is usually built with museums displaying their heritage nearby, so that people canexplore and learn more about the local historical background and artifacts of the place.The abandoned Iec Long Firecracker Factory in Taipa Center, Macau has been on hold formany years and has also been used as a war game venue that resulted in scratches on thewalls of the dilapidated old heritage buildings. Recently, the Macau government has finalizedits plans for the revitalization of this local heritage site. Due to its dispersed layout andsurrounding landscape, there are some design constraints around the preservation of thisimportant heritage site. The design for high cultural value land should not only consider thepreservation and renovation of old buildings but also consider more ways to effectively usethe site as an important public venue for the city.For developing the methodologies of this project, several concepts and case studies wereanalyzed to extract ideas that can be referenced and to unveil strategies for designing apossible solution to this problem. This dissertation intends to create a model for developingand integrating architectural design into this heritage site and will study the spacearrangements for both the indoor space and the outdoor space within the concept of afragmented space integration. Fragmented space, means that a place is designed using adecentralized layout. This conceptualization of a design can preserves the original appearance of the cultural value of land and at the same time, the space can be used moreefficiently to create a circulation for the public to visit and enjoy the location
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; articulation architecture; decentralized layout; functional museum; integration with architecture; spatial narrative

CUSTOM CLUSTER: DEMAND-DRIVEN VERTICAL HOUSING ARCHITECTURE - Un, Ka Kin (University of Saint Joseph, 2023)
Vertical housing is essential for modern cities because of its efficiency in using space (Wang, J. Murakami, A. 2019). The architecture of vertical housing is often determined by developers and designers. Therefore, the architecture of the building is fixed, and the end users are not involved nor can they influence its final appearance. For residential buildings, the unit sizes are based on market demand at a given point in time, which does not reflect the dynamic needs of the population as they evolve and may result in a mismatch between the supply and the demand for housing. The design of housing towers that have demographic characteristics and family size is dependent on housing size and can be very uncharacteristic and repetitive. The research question identified and addressed in this study is: How can residential buildings meet the evolving demand for housing units? Based on this question, this research paper develops a prototype for residential to resolve the dilemma between the supply and the demand in terms of the apartment size and layout. This research is a project-oriented project that focuses on residential that reflects the different family sizes required to be housed in the building and is combined with the open building method to maximize building performance. Ultimately, this research represents a meaningful innovation for market-driven architecture and defines architectural design based on the changing needs of the population using the open construction method. It also provides an opportunity to improve the design efficiency and develop a method for future growth, upgrades, and user needs. It may also be able to reflect the current housing ratio of the residential building. This work can be further explored to verify its effectiveness for other housing types and community living spaces
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; Vertical residential design; demand-driven architecture; form follows function; open building; residential clusters; stacking design

Plugin Program Reconfigurable Architecture System For Sustainable Future - Au Yeung, Kam Sheung (University of Saint Joseph, 2023)
The primary research focus of this dissertation revolves around the concept of a "plugin" program. It raises a fundamental question about whether a building can attain long-term usability through metabolic flexibility (plugin units and their reconfigurable space), promoting adaptability (accommodating various program transfers), and meeting sustainable future criteria. Specifically, this dissertation inquires whether this "plugin" building design, with its reconfigurable units and metabolic system, can adapt to different spatial programs and become sustainable architecture
Keywords: Building program transfer; Metabolism Architecture; Plugin capsule units; Reconfigurable; Sustainable Architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph